Making habits measurable beyond what they are not: A focus on associative dual-process models. (November 2022) - Watson, Poppy; O'Callaghan, Claire; Perkes, Iain; Bradfield, Laura; Turner, Karly
Abstract: Habits are the subject of intense international research. Under the associative dual-process model the outcome devaluation paradigm has been used extensively to classify behaviours as being either goal-directed (sensitive to shifts in the value of associated outcomes) or habitual (triggered by stimuli without anticipation of consequences). This has proven to be a useful framework for studying the neurobiology of habit and relevance of habits in clinical psychopathology. However, in recent years issues have been raised about this rather narrow definition of habits in comparison to habitual behaviour experienced in the real world. Specifically, defining habits as the absence of goal-directed control, the very specific set-ups required to demonstrate habit experimentally and the lack of direct evidence for habits as stimulus-response behaviours are viewed as problematic. In this review paper we address key critiques that have been raised about habit research within the framework of the associative dual-process model. We then highlight novel research approaches studying different features of habits with methods that expand beyond traditional paradigms. Highlights: Associative dual-process framework has been useful for study of habits. Issues with outcome devaluation paradigm as main diagnostic test for habit. Absence of goal-directed control is a narrow (negative) definition of habit. We address many of the issues and suggest possible experimental improvements. Theoretical reasons for why we lack direct evidence for stimulus-response habits. Highlight some of novel ways to measure habit beyond traditional paradigms.